KEBIJAKAN DAN IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DI SEKOLAH BERBASIS ISLAM - Rachmadian Choirunnisa; Titi Kadi (STKIP Subang, 2026)
This study aims to analyze the policy and implementation of multicultural education in Islamic schools. Multicultural education is crucial in the context of Indonesia's diverse society, encompassing religion, culture, ethnicity, and language. The research method used was a qualitative approach with a case study, using observation, interviews, and documentation as data collection techniques. The results indicate that multicultural education policies in Islamic schools are implemented through the integration of values ​​of tolerance, inclusivity, and respect for differences in the curriculum, learning activities, and school culture. Furthermore, the role of teachers as role models and facilitators is crucial for the successful implementation of multicultural values. Challenges include limited teacher understanding, cultural resistance, and a lack of specific policy support. Therefore, policy strengthening, teacher training, and curriculum development that are more responsive to diversity are needed.